PENGARUH MODEL PEMBELAJARAN JIGSAW DENGAN MEDIA WEBSITE PUZZLE MAKER TERHADAP MINAT BELAJAR SISWA DI SMAN 8 KOTA JAMBI - Marlina Marlina; Ervan Johan Wicaksana; Andre Mustofa Meihan (STKIP Pesisir Selatan, 2026)
This study aims to examine the effect of the Jigsaw learning model assisted by the Website Puzzle Maker media on students’ learning interest in history subjects at SMAN 8 Kota Jambi. This research employed a quantitative approach with a quasi-experimental design. The sample consisted of two classes, namely class XI F6 as the experimental group and class XI F3.2 as the control group, each comprising 35 students. The research instrument used was a learning interest questionnaire consisting of 15 statements that had been tested for validity and reliability using Pearson Product Moment correlation and Cronbach’s Alpha. The data were analyzed using an Independent Samples t-test with SPSS software, preceded by normality and homogeneity tests. The results showed that the average learning interest score of the experimental class was 60.09, while the control class was 62.51. The normality and homogeneity tests indicated that the data were normally distributed and homogeneous. The Independent Samples t-test results showed a significance value of 0.247 > 0.05, meaning that H₀ was accepted and H₁ was rejected. Therefore, it can be concluded that there is no significant effect of the Jigsaw learning model assisted by the Website Puzzle Maker media on students’ learning interest. However, this learning model still has potential to enhance student engagement if implemented more optimally and continuously in the learning process